2012
DOI: 10.1016/j.physletb.2011.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Generalized parton distributions of the photon for nonzero skewness

Abstract: Abstract. We extend the framework of combinatorial model categories, so that the category of small presheaves over large indexing categories and ind-categories would be embraced by the new machinery called class-combinatorial model categories.The definition of the new class of model categories is based on the corresponding extension of the theory of locally presentable and accessible categories developed in the companion paper [10], where we introduced the concepts of locally class-presentable and class-access… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Uteroglobin (SCGB1A1) is a multifunctional, hormonally regulated globular protein associated with a variety of cancers. [27,35,36] Displaying involvement in both hormonal response and immunity, its functions remain largely unknown. [35] In recent studies, expression analysis and immunohistochemical staining of ovarian tumor tissues identified no significant difference in uteroglobin levels between ovarian cancer tissue and normal ovarian tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Uteroglobin (SCGB1A1) is a multifunctional, hormonally regulated globular protein associated with a variety of cancers. [27,35,36] Displaying involvement in both hormonal response and immunity, its functions remain largely unknown. [35] In recent studies, expression analysis and immunohistochemical staining of ovarian tumor tissues identified no significant difference in uteroglobin levels between ovarian cancer tissue and normal ovarian tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The helicity dependent twist-two and twistthree GPDs in light-front Hamiltonian QCD for a massive dressed quark target has been presented in [44]. The general properties of GPDs in QED models have been studied in both momentum and transverse position as well as longitudinal position spaces [10,55]; the impact parameter representation of the GPDs have been investigated in a QED model of a dressed electron [11]. The moments of the GPDs have been calculated on lattice [56,57,58,59].…”
Section: Introductionmentioning
confidence: 99%
“…More recently the deeply virtual Compton scattering (DVCS) amplitude with the photon target ( Fig.1) was calculated, and then GPD and GDA functions characterizing quark content of the photon were extracted. DVCS on a photon is therefore a kind of toy model for QCD which has been recently generalized for the case of impact parameter dependent GPDs [7,8]. This provides an incredible opportunity to test our current mathematical tools of GPDs studies.…”
Section: Introductionmentioning
confidence: 99%